Implementation of Lean Construction and Risk Management for Waste Identification in the Jragung Dam Construction Project Package 2 - Hanif Adriantama Muhammad; Agung Wibowo Mochammad; Utomo Dwi Hatmoko Jati (E3S Web of Conferences)
PT Wijaya Karya (Persero) Tbk, a leading state-owned construction enterprise, faces significant waste management challenges that have caused financial losses in previous projects. This study applies lean construction and risk management to identify waste and risks in the Jragung Dam Construction Project Package 2. Waste identification began with brainstorming sessions with the project management team, followed by a borda questionnaire to prioritize waste using the pareto principle. 5-whys discussions were then used to determine the risks causing critical waste. These risks were categorized using the Risk Breakdown Structure (RBS) and analysed through Failure Mode and Effect Analysis (FMEA), with risks plotted on a cartesian diagram based on Risk Priority Number (RPN) and Risk Severity Value (RSV). The four critical waste types identified were defects (20.05%), waiting (19.80%), over-processing (17.79%), and overproduction (14.04%). The highest-priority risks were unfinished diversion channels (RPN 108, RSV 36), geological issues found (RPN 105, RSV 35), and design revision (RPN 96, RSV 32). The benefit of this research is a systematic approach for identifying waste through lean construction and risk management principles, facilitating targeted waste identification. This process is expected to help the company make informed decisions, enhancing project efficiency and reducing potential financial losses.